1993
DOI: 10.1017/s0021932000020654
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and environmental determinants of child survival in Bangladesh

Abstract: Differentials in child survival in Bangladesh have been examined using a number of socioeconomic and environmental factors on data from the 1989 Bangladesh Fertility Survey. Multivariate analysis reveals that both wife's and husband's education and household electricity show a significant positive association with child survival. The respondent's working status exerts a significant negative influence. Wife's education has a greater influence on child survival in Bangladesh than that of husband's education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…This finding is consistent with similar findings from Zimbabwe (26), Malawi (27) and south western Uganda (25), all of which have consistently shown that children from landless households or those from households with very small land holdings are at high risk of malnutrition. These findings lend support to the theory that poverty is a very important determinant of malnutrition (28,29).…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with similar findings from Zimbabwe (26), Malawi (27) and south western Uganda (25), all of which have consistently shown that children from landless households or those from households with very small land holdings are at high risk of malnutrition. These findings lend support to the theory that poverty is a very important determinant of malnutrition (28,29).…”
Section: Discussionsupporting
confidence: 84%
“…Some other studies have reported strong relationship between nutritional status of children and level of education of their mothers (8,10). However, a few studies in Bangladesh have comprehensively examined the relationship between their socio‐economic and illness characteristic and nutritional status (7,8). Severely malnourished children are at higher risk for developing life‐threatening illnesses and require long‐term nutritional rehabilitation.…”
Section: Introductionmentioning
confidence: 94%
“…The percentage of urban residing population is 28.1 while that of rural is 71. 9. As in many developing region of the world the core health problem in Bangladesh are related to high fertility malnutrition and communicable disease about 1030000 children less than 5 year of age die every year.…”
Section: Imentioning
confidence: 99%